A Research on Dynamic Friction Compensation of High-speed Linear motor - Xuan Cui; Yuan Ji; Hua Sun (Institute of Advanced Engineering and Science, 2012)
The tracing precision of high-precise linear motor is greatly influenced when moved at a low speed because of the friction. This paper aims at a practical angle, on the base of traditional Stribeck friction model, we added in position parameter to set up a new model .According to the new model, we designed out the forward back controller to identificate and compensate the system. at last, the stability of systems has also been analyzed by using Liapunov functions and LaSalle Invariance Principle.The simulation results shows our model has improved the tracing performance. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1645